Analysis of algorithmic problems solved in Olympiads: stands of students and experts - Blonskis, Jonas; Dagienė, Valentina; Plukas, Kostas (Lietuvos matematikos rinkinys, 2003)
Olympiads (National, Baltic, International) in Informatics are well-known among students. Various algorithmic problems are given to students. The paper deals with the problems from the latest three years. Methods of solving problems are discussed from mathematical and programming perspectives. The main attention is paid to selection, development and application of proper data structures.